Maternal and fetal outcomes in pregnancies complicated by renal disease: a single-centre observational study - Krishnamurthy, Aparna; Ashok Mahajan, Rahul; Magdum, Hrishikesh; Chawla, Sushil; N. M., Anupam Kapur; Behera, Vineet; Ananthakrishnan, Ramamoorthy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Renal disease in pregnancy poses significant risks for both mother and fetus, with increased rates of maternal morbidity, fetal growth restriction, preterm delivery, and adverse neonatal outcomes. In India, women comprise nearly half the renal disease burden, and 3-5% of them conceive. This study evaluates the clinical profile, maternal, and fetal outcomes of pregnancies complicated by renal disease. Methods: A retrospective observational study was conducted at a tertiary care hospital in Western India between February 2020 and July 2023. All pregnant women with documented renal disease or renal abnormalities were included. Data on demographics, comorbidities, renal parameters, obstetric outcomes, and complications were analysed. Results: Of 44 screened women, 36 met inclusion criteria. Mean age was 29.2±4.7 years; 58.3% were multigravida. Hypertension (27.8%) and proteinuria >1000 mg/day (16.7%) were significant predictors of adverse fetal outcome (p<0.05). Maternal age >30 years and multigravida status were significantly associated with caesarean delivery (p<0.05). Preterm delivery occurred in 41.7%, and intrauterine growth restriction in 25%. Conclusions: Pregnancies complicated by renal disease represent a high-risk group requiring multidisciplinary management. Preconception counselling, optimal blood pressure control, and close antenatal surveillance can improve outcomes. Larger multicentric studies are needed for more definitive guidance.